Microfauna- and sedimentology-based facies analysis for palaeolandscape reconstruction in the back-barrier area of Norderney (NW Germany). (19th February 2021) - Elschner, Annastasia; Scheder, Juliane; Bungenstock, Friederike; Bartholomä, Alexander; Becker, Thorsten M; Capperucci, Ruggero M; Enters, Dirk; Karle, Martina; Schlütz, Frank; Wehrmann, Achim; Hoffmann, Gösta
Abstract: Palaeolandscape reconstructions at the German North Sea coast are essential for the understanding of coastal changes and dynamic landscape-forming processes. This study contributes to reconstructing Holocene coastal changes in the back-barrier area of the East Frisian island of Norderney and draws conclusions on the local palaeogeography. Five sediment cores were analysed in terms of sedimentology (grain-size distribution), geochemistry (TOC, TIC, N, C/N), microfauna (foraminifers and ostracods) and 13 radiocarbon dates. In order to identify driving environmental factors and support the facies interpretation, multivariate statistics (PCA) were carried out. Additional cores from the surrounding area (WASA Project and 'Landesamt für Bergbau, Energie und Geologie' (LBEG) Hannover) enabled correlation of the investigated cores over a transect of ~6 km, showing six depositional environments, which can be used for landscape reconstruction. Deposition starts with periglacial (aeolian and glaciofluvial) Pleistocene sediments, with subsequent pedogenesis followed by swamp conditions that develop into a salt marsh. The overlying tidal-flat sediments are partially cut by (fossil and recent) channel deposits. A hiatus at the base of the tidal-flat deposits that spans some 3000 years hints at their reworking caused by a combination of antrophogenic coastal protection measures and the impact of storms. Furthermore, based on the profile correlation and the age data, a widespread salt-marsh area with a minimum age of ~4000 cal BP is defined for the 'Hohes Riff' in the southwestern back-barrier of Norderney Island.